Forest fire monitoring, detection and decision making systems by wireless sensor network - Liu, Y.; Liu, Y.; Xu, Honglei; Teo, Kok Lay (2018)
© 2018 IEEE. Wireless Sensor Networks (WSNs) can be used for many applications, such as industrial automatic control, remote environmental monitoring and target tracking. The similar system is promising applications in forest fires can make a real-time monitoring and detection. Wireless sensor network consists of numerous small nodes in most situations, which small nodes are deployed in remote and inaccessible hostile environments or over large geographical areas. The large number of small nodes sense environmental changes and report them to cluster head node over network architect, which the deployment and maintenance should be easy and scalable. A new approach for forest fire monitoring and detection was present in this paper, which it is by using data aggregation in wireless sensor network. The proposed approach can provide faster and efficiently reaction to forest fires while consuming economically WSN's energy, which has been validated and evaluated in extensive simulation experiments.